HUBUNGAN ANTARA IBU BEKERJA DENGAN PENYAPIHAN DINI PADA ANAK USIA 1-2 TAHUN DI KELURAHAN BUGUL LOR KECAMATAN BUGUL KIDUL KOTA PASURUAN - Frilasari, Heni; Triseptiani, Galih (JURNAL KEPERAWATAN SEHAT, 2011)
Malnutrition in children aged under 2 years can be minimized through exclusive breastfeeding. However, working mothers only breastfeed while on leave from work about 3-5 months so that after that she immediately weaning her baby. Research objectives is to determine the correlation between working mothers with early weaning in children aged 1-2 years in the Bugul Lor Village Bugul Kidul District Pasuruan. Research design using analytic crossectional approach. Population was all mothers who have children aged 1-2 years in the the Bugul Lor Village Bugul Kidul District Pasuruan as many as 34 mothers taken using purposive sampling technique. Data analyzed using chi-square tests. From the analysis of data obtained p = 0.006 <0.05 means there is a correlation between working mothers with early weaning in children aged 1-2 years in the Bugul Lor Village Bugul Kidul District Pasuruan. From the results of research can be concluded that the majority of respondents are working mothers and children aged 1-2 years were weaned early. Mom was always expected to breastfeed exclusively at children so children are not exposed to diseases, especially leukemia and lymphoma in children.Keywords: Working Mother, Early weaning, Children Ages 1-2 years